Concise encyclopaedic dictionary of ceramics: pottery, glass, vitreous enamels, refractories, clay building materials, cement and concrete, electroceramics, special ceramics - 258708 Dodd, A. E. (Amsterdam, The Netherlands: Elsevier Pub., 1967)
PSZKLL